ISTILAH-ISTILAH MAKANAN DAN MINUMAN DALAM BAHASA INGGRIS DAN BAHASA TOBELO (SUATU ANALISIS KONTRASTIF) - Sumanti, Peggy Lady Claudia; Rattu, Jultje A.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œTerms of Food and Beverage in English and Tobelo language (A Contrastive Analysis)â€. The objectives of this research are to identify and classify the types of food and beverages in English and Tobelo language and o analyse the differences and similarities of the terms of food and beverages between English and Tobelo language. This research uses a descriptive method. The data of food and beverages in English were collected from skripsi, journal, or article from the internet, while the data in Tobelo language were collected by interviewing informants by phone calls, furthermore in taking the data pictures of food and beverages in Tobelo language, the writer conducted picture searching of food and beverages by the internet and also took some pictures from the traditional markets and then confirmed the data of the images taken were appropriate and correct with the intended data to the informants. The collected data have been analyzed by using the theories from Frisch in Hickersonâ€™s and Foleyâ€™s and then to get a contrastive analysis the writer uses the theory of Ladoâ€™s also to find out the difference and similarities of the two different languages. The result shows that the data of English food consist two types those are solid food and beverages/drink. Tobelo language consist of three groups those are solid food, liquid food, and beverages/drink. English food and beverages has 8 ways of making food and beverages, Tobelo language has 9 ways. English food and beverages has 8 types of basic food and beverages ingredient, while in Tobelo language has 10 types of basic food and beverages ingredient. The differences found are in English categories has no liquid food while in Tobelo language has. In English language have many kinds of bread while in Tobelo language have many kinds of cakes/cookies. In the way of food and beverages are made, Tobelo language has nonofu/fufu(smoke/fumigation) but in English has not. In the basic ingredient of staple food in English has wheat and bread while in Tobelo language has rice and sagu(sago)._______________________Keywords: Terms, Food and Beverages, English Language, Tobelo Language, Contrastive Analysis.Â